A review of central and peripheral limitations to endurance exercise performance on the road to the Milano-Cortina 2026 Olympics - Skattebo, Ø.; Martin-Rincon, M.; Calbet, J. A. L.; Hallén, J.; Holmberg, H.-C. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Performance in endurance sports reflects a complex interplay between physiological, biomechanical, neuromuscular and psychological factors, nutrition, and environmental conditions. This review focuses on physiological factors, particularly on the determinants of maximal oxygen uptake ( VO2max), its fractional utilization during competition, and examines how these interact with sport-specific demands and conditions anticipated at the Milano-Cortina 2026 Winter Olympics. We highlight that systemic O2 delivery, determined by the product of cardiac output and arterial O2 content, is the primary limiting factor of VO2max in elite athletes. However, invasive data on elite female athletes are scarce, and more research is needed. Well-developed peripheral characteristics, such as a high mitochondrial density and capillarisation, are important determinants of fractional utilization of VO2max, but also support high muscle O2 extraction, which may reach values above 95% in elite endurance athletes, including cross-country skiers. However, most values of fractional utilization of VO2max in the literature are calculated estimates based on performance determinants and race times, and more research with direct, continuous O2 uptake measurements during simulated competitions is needed. In endurance sports with undulating terrain race profiles (uphill, downhill, flats), such as cross-country skiing and biathlon, the resulting intermittent exercise intensity creates substantial fluctuations in external power output. As a result, O2 demands may reach 100%-160% of VO2max in uphill sections, facilitated by transient but profound anaerobic energy contributions. Thus, the ability to recover anaerobic energy sources in downhill sections and repeatedly use them throughout the race emerges as a critical performance determinant and an avenue for further research, as well as how these abilities influence fractional utilization of VO2max in intermittent sports. Environmental factors, including moderate altitude (Biathlon will be held in Antholz at ~1650 m) and cold temperatures, exert modest but relevant influences on performance. Understanding these integrative mechanisms is essential for optimizing training and competition strategies for endurance sports at the Winter Olympics and beyond.